Digital signal conditioning of bioelectric signals a study of digital filter implementation. - Rodriguez, S.V.
This paper presents possible ways of implementing digital Finite Impulse Response (FIR) filters in microprocessors to perform signal conditioning on biomedical electropotential signals, specifically electromyogram (EMG) and electrocardiogram (ECG). Digital filters are useful for these applications because of the flexibility offered by these filters as compared to their analog counterparts. This study focuses on the FIR type of digital filters because of their potential to minimize the distortion introduced to a signal. Different FIR filter design implementations are presented in order to come up with a comparative performance of the different implementations. The filters will be compared based on performance, accuracy, cost and complexity. Requirements and recommendations will be made describing various alternatives in digital filter implementation.